Adverse childhood experiences and sexual victimization in adulthood. (January 2016) - Ports, Katie A.; Ford, Derek C.; Merrick, Melissa T.
Abstract: Understanding the link between adverse childhood experiences (ACEs) and sexual victimization (SV) in adulthood may provide important information about the level of risk for adult SV and sexual re-victimization among childhood sexual abuse (CSA) survivors. In the present paper, we explore the relationship between ACEs, including CSA, and SV in adulthood. Data from the CDC-Kaiser ACE Study were used to examine the effect of experiences of early adversity on adult SV. Adult HMO members ( n = 7, 272) undergoing a routine health exam provided detailed information about ACEs that occurred at age 18 or younger and their experiences of SV in adulthood. Analyses revealed that as ACE score increased, so did risk of experiencing SV in adulthood. Each of the ACE variables was significantly associated with adult SV, with CSA being the strongest predictor of adult SV. In addition, for those who reported CSA, there was a cumulative increase in adult SV risk with each additional ACE experienced. As such, early adversity is a risk factor for adult SV. In particular, CSA is a significant risk factor for sexual re-victimization in adulthood, and additional early adversities experienced by CSA survivors may heighten adult SV risk above and beyond the risk associated with CSA alone. Given the interconnectedness among various experiences of early adversity, adult SV prevention actions must consider how other violence-related and non-violence-related traumatic experiences may exacerbate the risk conferred by CSA on subsequent victimization.